2013
DOI: 10.5194/bg-10-3479-2013
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variation in the epibenthic megafauna at the shallowest station of the HAUSGARTEN observatory (79° N, 6° E)

Abstract: Epibenthic megafauna play an important role in the deep-sea environment and contribute significantly to benthic biomass, but their population dynamics are still understudied. We used a towed deep-sea camera system to assess the population densities of epibenthic megafauna in 2002, 2007, and 2012 at the shallowest station (HG I, ∼1300 m) of the deep-sea observatory HAUSGARTEN, in the eastern Fram Strait. Our results indicate that the overall density of megafauna was significantly lower in 2007 than in 2002,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 52 publications
(73 reference statements)
0
16
0
Order By: Relevance
“…m 22 ). Likewise, Meyer et al (2013) reported similar densities (mean 16.5-19.2 ind. m 22 ) of ophiuroids as Soltwedel et al (2009) at 798 N, 1200 m in Fram Strait in the first 2 yr of an inter-annual study of megabenthos; whereas during the last year, the density was significantly higher, (mean 49.6 ind.…”
Section: Methane Derived Carbonate Outcrops-a Substrate For Megafaunamentioning
confidence: 67%
See 2 more Smart Citations
“…m 22 ). Likewise, Meyer et al (2013) reported similar densities (mean 16.5-19.2 ind. m 22 ) of ophiuroids as Soltwedel et al (2009) at 798 N, 1200 m in Fram Strait in the first 2 yr of an inter-annual study of megabenthos; whereas during the last year, the density was significantly higher, (mean 49.6 ind.…”
Section: Methane Derived Carbonate Outcrops-a Substrate For Megafaunamentioning
confidence: 67%
“…Based on morphotypes and appearance, we suggest at least three different species of zoarcids are represented in the photos: (1) Lycodes squamiventer Jensen, 1904, (2) Lycodonus flagellicauda (Jensen, 1902), and (3) Lycodes frigidus Colett, 1879. They are all known at the VR region and recognized from Arctic waters (Bergmann et al ; Meyer et al ). Soft‐bottom anemones, ampharetid‐like polychaetes (hereafter referred to as ampharetids), and large buccinoid gastropods (possible Colus sp.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Images were recorded using a downward-facing towed camera system, the Ocean Floor Observation System (OFOS), and specifics are reported by Meyer et al (2013) for 2012 sampling. The target altitude was 1.5 m, and each image shows approximately 3 to 4 m 2 of the seafloor.…”
Section: Image Collectionmentioning
confidence: 99%
“…Photographic surveys were carried out during the expedition ARK-XXVII/3 in summer 2012 (2 August-29 September) in the Nansen and Amundsen basins (Fig 1). The seafloor was photographed using a towed Ocean Floor Observation System (OFOS) [75]. Nine stations (one transect per station) were performed: four in the Nansen Basin between 83-84°N and 18-110°E at depths 3571-4066 m, and five in the Amundsen Basin between 83-89°N and 56-131°E at depths 4041-4384 m (Fig 1).…”
Section: Methodsmentioning
confidence: 99%